Workers' flows and real wage cyclicality - Anabela Carneiro; Pedro Portugal (Institute for the Study of Labor (IZA), 2007)
This study investigates real wage cyclicality in Portugal for the years of 1986-98, addressing the heterogeneity in wages responses to aggregate labor market conditions for workers' hirings and separations. The results exhibit a moderate procyclical behavior of real wages for continuously employed workers, in particular, for job stayers. For workers' accessions a strongly procyclical behavior in wages was observed, which is consistent with the idea that entry wages are much more procyclical than current wages. This empirical evidence suggests that even micro-data estimates of real wage cyclicality may conceal a strong procyclical wage behavior, when heterogeneity on wages responses to aggregate conditions between employed workers and hirings and separations is not taken into account
urn:nbn:de:101:1-20080422161
Keywords: 330; Arbeitsmobilität; Reallohn; Lohnstruktur; Personalbeschaffung; Portugal